Analysis of the Use of Financial Reports as a Basis for Management Decision Making (Case Study of PT PLN (Persero) UP3 South Makassar - Reksy Aurelia Ardana; Andi Jam’an; Amran Amran (CV. AFDIFAL MAJU BERKAH, 2025)
This study aims to analyze the use of financial statements as a basis for management decision making at PT PLN (Persero) UP3 Makassar Selatan. Financial statements are an important tools in assessing company performance and supporting strategic and operational decisions. The research method used is a case study with a descriptive qualitative approach. The data analyzed are in the form of financial statements for the period 2019–2022 using financial ratios that include liquidity, solvency, activity, and profitability ratios. The results of the study indicate that although the company shows sufficient capabilities in terms of profitability and activity, there are significant fluctuations in the liquidity and solvency ratios, especially in the debt to equity ratio which shows a high dependence on debt. Financial ratio analysis provides a clear picture of the company's financial condition and is an important basis for management decision making, such as operational efficiency, accounts receivable management, and investment strategy. Therefore, optimal use of financial statements can increase the effectiveness of managerial decision making and support the sustainability and growth of the company.